2014
DOI: 10.1177/0022034514529974
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Efficacy of Exogenous Nitric Oxide on Periodontal Pathogens

Abstract: Current treatments for periodontitis (e.g., scaling/ root planing and chlorhexidine) have limited efficacy since they fail to suppress microbial biofilms satisfactorily over time, and the use of adjunctive antimicrobials can promote the emergence of antibiotic-resistant organisms. Herein, we report the novel application of nitric oxide (NO)-releasing scaffolds (i.e., dendrimers and silica particles) as anti-periodontopathogenic agents. The effectiveness of macromolecular NO release was demonstrated by a 3-log … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 27 publications
9
64
1
1
Order By: Relevance
“…Prior works have demonstrated that dietary nitrate or exogenous NO exerts antimicrobial effects and can alter oral microbiome composition . However, dietary nitrates did not induced significant differences in fecal microbioma composition or diversity .…”
Section: Discussionmentioning
confidence: 75%
“…Prior works have demonstrated that dietary nitrate or exogenous NO exerts antimicrobial effects and can alter oral microbiome composition . However, dietary nitrates did not induced significant differences in fecal microbioma composition or diversity .…”
Section: Discussionmentioning
confidence: 75%
“…The reduced toxicity observed for NO-releasing long alkyl chain dendrimers, while maintaining superior anti-biofilm activity, demonstrates their potential utility as dental caries therapeutics. Indeed, the toxicity levels exhibited by the NO-releasing octyl- and dododecyl-modified dendrimers is comparable to that of clinical doses of chlorhexidine, which have been found to reduce HGF-1 cell viability by ~80% after 2 h [33]. …”
Section: Discussionmentioning
confidence: 99%
“…More recently, we reported on the controlled delivery of exogenous NO to kill S. mutans [32, 33]. In these studies, large instantaneous concentrations of NO were required to eradicate S. mutans .…”
Section: Introductionmentioning
confidence: 99%
“…For example, NO-releasing G1-PAMAM dendrimers exhibit stronger bactericidal action relative to silica nanoparticles of similar NO-release properties (attributable to enhanced bacterial-scaffold association of the dendritic scaffold). [87] However, the synthetic cost (e.g., synthesis and purification) of dendrimers is much greater than that of silica, with significant scale up and manufacturing hurdles. As a potential solution, Yang et al reported the synthesis of NO-releasing hyperbranched polymers via a one-pot reaction in bulk.…”
Section: Discussionmentioning
confidence: 99%